Keragaan Agronomi dan Potensi Hasil Inbred Generasi S8 Jagung (Zea mays L.) untuk Hibrida Harapan Baru: Agronomic Performance and Yield Potential of S8 Generation lines of Corn (Zea mays L.) for the New Promising Hybrid - Taufiq Hidayatullah; Irfan Suliansyah; Etti Swasti; Nurwanita Ekasari Putri; I Made Jaya Mejana (Politeknik Pertanian Bogor, 2023)
High yielding corn breeding program is an alternative to meet national needs. Characterization is one of the essential stages in a corn breeding program. This research aims to evaluate agronomic characters and yield potential of the parent lines to be used as a basis for the hybrid variety development program. This research was conducted from May to October 2023 at the Koto Tingga Experimental Station, Padang, West Sumatra Province. There are 5 promising corn lines used in this study with a one-factor completely randomized block design with 3 replications, therefore there were15 experimental units. The results shows that lines significantly affected on all characters except the number of cobs per plant and yield potential. The Mz1 line had the highest yield potential (3,7 tons ha-1), followed by the Mz5 line (3,4 tons ha-1). These two lines have relatively medium plant height (221,6–246,3 cm), early harvest maturity (94,2–99,9 DAP), and medium to high 100–grain weight (28,4–37,9 g). These two lines have the potential to be further developed as crossing parental.